1996
DOI: 10.1046/j.1570-7458.1996.00095.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of insecticide residues on primary parasitoid and hyperparasitoid foraging behaviour in the laboratory

Abstract: The behaviour of Aphidius rhopalosiphi DeStefani-Perez (Hymenoptera: Braconidae) was recorded in laboratory bioassays in the presence and absence of both residues of honeydew from the English grain aphid, Sitobion avenae (F.) and the pyrethroid insecticide, deltamethrin. Insecticide concentrations ranged from the field recommended dose rate (6.25 g ai/ha in 200 l water) to 1/16th of field rate. Parasitoids responded strongly to patches of honeydew on filter papers, however the addition of increasing concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 32 publications
3
36
1
1
Order By: Relevance
“…Irving and Wyatt, 1973;Perera, 1982;Jiu and Waage, 1990;Longley and Jepson, 1996;Umoru et al, 1996). However, we did not observe parasitoids attempting to escape from the observation cage during this study.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Irving and Wyatt, 1973;Perera, 1982;Jiu and Waage, 1990;Longley and Jepson, 1996;Umoru et al, 1996). However, we did not observe parasitoids attempting to escape from the observation cage during this study.…”
Section: Discussionmentioning
confidence: 74%
“…However, insecticides such as organophosphates, carbamates, and synthetic pyrethroids are generally highly toxic to biological control agents, due to their broad spectrum of activity (Croft, 1990). Other insecticides that do not appear to kill natural enemies, may also have sub-lethal effects, such as altered behavior, reduced reproduction, and reduced longevity, on natural enemies (Jacobs et al, 1984;Elzen, 1989;Croft, 1990;Longley and Jepson, 1996). In IPM, therefore, it is important to examine the possible disruptive effects of candidate insecticides on beneficial insects, and to determine the insecticides compatible with key biological control agents (Stapel et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Konsentrasi dengan metode ini digunakan karena masing-masing nilai konsentrasi pada metode kontak dan oral menunjukkan nilai 95% FL yang tumpang tindih yang menunjukkan tidak berbeda nyata. Metode paparan pestisida dengan aplikasi topikal, oral, residu, atau studi lapangan telah banyak digunakan untuk melihat responsnya terhadap musuh alami (Longley & Jepson 1996;Longley 1999;Desneux et al 2005;Wang et al 2008;Liu et al 2010;Fernandes et al 2010). Masing-masing pendekatan memberikan informasi terhadap dampak pestisida terhadap musuh alami.…”
Section: Pembahasanunclassified
“…Several studies have reported pyrethroid repellence. For example, Longley and Jepson (1996) detected lower percentages of parasitism of Aphidius rhopalosiphi (De Stefani-Perez) (Hymenoptera: Aphidiidae) to aphids previously treated with deltamethrin. In this study, organisms exposed to cypermethrin consumed very little of the treated diet during the first 24 h of testing.…”
Section: Invertebrate Reproduction and Development 203mentioning
confidence: 99%